2022
DOI: 10.1002/nau.25075
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of specific white matter tracts is associated with neurogenic lower urinary tract dysfunction in women with multiple sclerosis

Abstract: Objective To identify specific white matter tracts (WMTs) whose disruption is associated with the severity of neurogenic lower urinary tract dysfunction (NLUTD) in two independent cohorts of women with multiple sclerosis (MS) and NLUTD. Methods Cohort 1 consisted of twenty‐eight women with MS and NLUTD. The validation cohort consisted of 10 women with MS and NLUTD. Eleven healthy women served as controls. Participants of both MS cohorts had the same inclusion and exclusion criteria. Both MS cohorts and the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…Subsequent studies should explore and compare the roles of optimized 7T-FLAIR and 7T-MTw imaging[ 44 ]. A recent study aimed to pinpoint white matter tracts (WMTs) associated with the severity of neurogenic lower urinary tract dysfunction (NLUTD) in women with MS[ 45 ]. The primary cohort included 28 women with MS and NLUTD, and a validation cohort comprised 10 women with similar conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies should explore and compare the roles of optimized 7T-FLAIR and 7T-MTw imaging[ 44 ]. A recent study aimed to pinpoint white matter tracts (WMTs) associated with the severity of neurogenic lower urinary tract dysfunction (NLUTD) in women with MS[ 45 ]. The primary cohort included 28 women with MS and NLUTD, and a validation cohort comprised 10 women with similar conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The primary cohort included 28 women with MS and NLUTD, and a validation cohort comprised 10 women with similar conditions. Both cohorts underwent clinical assessments and functional MRI protocols, with the validation cohort additionally undergoing a 7T fMRI scan[ 45 ]. The study identified a robust correlation between fractional anisotropy and mean diffusivity of specific WMTs and clinical parameters related to NLUTD symptoms in women with MS, notably the right inferior cerebellar peduncle, left posterior limb of the internal capsule, and left superior cerebellar peduncle[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation